Cattle Raising and the Capixaba Agrarian Space: the Rise of the “Ox Domains” in Extreme North Espírito Santo - Neto, Jaime Bernardo (Geografares, 2016)
Discusses about the spreading of extensive bovine cattle raising in Espirito Santo from the decade of 1940, aiming to relate the factors that unleashed this phenom as well as it ́s reflexes over the capixaba agrarian space, particularly in it ́s Extreme North, based on the case study about Montanha ́s, Mucurici ́s and Ponto Belo ́s municipalities, where the extensive bovine cattle raising specialization had significant contribution in intensifying this area ́s land owning concentration and rural exodus in the last decades.Keywords: Bovine Cattle Raising - Agrarian Space - Espírito Santo.